An easy way to the preparation of multi-miktoarm star block copolymers via sequential double click reactions - Dag, Aydan; DAĞ, AYDAN; Durmaz, Hakan; Kirmizi, Volkan; Hızal, Gürkan; Tunca, Ümit (My University, 2010)
As a new synthetic route, we here employed sequential double click reactions involving azide-alkyne and Diels-Alder reactions for the preparation of multi-miktoarm star block copolymers by using the arm-first approach.